Molecular Analysis and Phenotypic Performances of BC3F2 Upland Rice Lines Containing Alt and Pup1 Loci - Mizan, Muhammad Rauful; Wirnas, Desta; Tasliah, nFN; Hidayatun, Nurul; Prasetiyono, Joko (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2019)
The challenges in upland rice cultivation are phosphorous (P) deficiency and aluminum (Al) toxicity, each controlled by Pup1 and Alt loci, respectively. Pyramiding the two genes into Indonesian rice varieties were previously done through Marker-Assisted Backcrossing method to obtain BC3F2 populations. The aims of this study were to analyze the BC3F2 upland rice lines containing the Alt and Pup1 loci molecularly (foreground and background analyses) and to test their phenotypic performances. Genetic materials tested included Dupa variety (donor of Alt) and three improved Indonesian genotypes (Dodokan-Pup1, Situ Bagendit-Pup1, and Batur-Pup1) as recurrent parents, Kasalath (donor of Pup1), and 300 BC3F2 lines from Dodokan-Pup1+Alt, Situ Bagendit-Pup1+Alt, and Batur-Pup1+Alt, respectively. The rice genotypes were selected individually using modified Yoshida nutrient solution, followed by foreground and background analyses. 150 out of 300 seedlings were selected and maintained until harvest in the greenhouse. Foreground analysis using markers (RM1361, RM12031, and Kas46-2) and tiller number performances resulted in 18 plants from BC3F2 Dodokan-Pup1+Alt, 30 plants from BC3F2 Situ Bagendit-Pup1+Alt, and 25 plants from BC3F2 Batur-Pup1+Alt still carrying Alt and Pup1 loci. Background analysis using molecular markers showed that the best individual lines of BC3F2 were number 56 for BC3F2 Dodokan-Pup1+Alt, number 32 or 70 for BC3F2 Situ Bagendit-Pup1+Alt, and number 20 for BC3F2 Batur-Pup1+Alt. The selected lines having both both Alt and Pup1 loci in homozygote condition with highest number of tiller per plant which are useful genetic materials for developing upland rice variety tolerance to low P and Al toxicity.